FRI0541 Influence of rheumatoid arthritis-related morning stiffness on productivity at work: results from a survey in 11 european countries. (23rd January 2014) - Mattila, K.; Buttgereit, F.; Tuominen, R.
Abstract : Background: RA has a substantial societal effect in terms of costs, disability and lost productivity, with much of the costs occurring outside the healthcare system (1, 2 ). However, the calculatedcosts of RA vary considerably depending on countries studied and methods used (3 ). Objectives: The objective of this study wasto evaluate the influence of morning stiffness on productivity at work and to estimate the work-related economic consequences of morning stiffness in 11 European countries. Methods: The original sample comprised 1061 RA patients from 11 European countries (Belgium, Denmark, Finland, France, Germany, Italy, Norway, Poland, Spain, Sweden and UK). They had symptoms of morning stiffness for more than six months, three or more times per week. Data were collected by interviews using a structured questionnaire translated into local languages. Women comprised 77.9% of the sample, the average age was 50.4 years and 84.3% had RA diagnosed for more than 2 years. Based on the average working time in EU countries (4 ) in all time-based cost estimates the numbers of active working hours per year was estimated to be 1568. The annual level of gross income reported by the patients was used to obtain individual time-based cost estimates. Results: Overall costs of RA-related morning stiffness was calculated to be 27712€ per patient per year, varying from 4965€ in Spain to 66706€ in Norway. On average 96% (77-99%) of the overall production losses were attributed to early retirement, with a markedly lower level (77%) in Italy than in other countries (p<0.0001). The proportion of patients who reported retirement due to morning stiffness showed considerable variation across the countries represented in the study, being relatively low in Italy but much higher in Finland, Denmark, UK and Poland. Also the productivity losses caused by late work arrivals, sick leave and working while sick were considerable. Overall, the annual cost of late arrivals (6-847€) was approximately half of the costs attributed to sick leave (0-1506€) and working while sick (0-1090€). Conclusions: Morning stiffness due to RA causes significant production losses and is a significant cost burden throughout Europe. There seem to be notable differences in the impact of morning stiffness on productivity between European countries. References: Kobelt G, Jönsson B. The burden of rheumatoid arthritis and access to treatment: outcome and cost-utility of treatments. Eur J Healh Econ 2008;8 (Suppl 2):S95-S106. Merkersdal S, Ruof J, Huelsemann J et al. Development of a matrix of cost domains in economic evaluation of rheumatoid arthritis. J Rheumatol 2001;28:657-661. Lundqkvist J, Kastäng F, Kobelt G. The burden of rheumatoid arthritis and access to treatment: health burden and costs. Eur J Health Econ 2008; 8 (Suppl2):S49-S60. Eurostat yearbook 2011. http://epp.eurostat.ec.europa.eu/portal/page/portal/product_details/publication?p_product_code=CH_06_2011 / accessed 25.10.2012. Acknowledgements: The survey was conducted by Ipsos MORI and sponsored by an educational grant from Mundipharma International Limited. Disclosure of Interest: K. Mattila: None Declared, F. Buttgereit Grant/research support from: Merck Serono & Horizon Pharma, Consultant for: Merck Serono, Horizon Pharma (formerly Nitec Pharma) & Mundipharma International Limited, Speakers bureau: Mundipharma International Limited, R. Tuominen Consultant for: Mundipharma International Limited, Speakers bureau: Mundipharma International Limited